The Intern – A Summer of Lust - Lust, Erika (Saga Egmont, 2022)
The Intern is the story of two sisters: Maddie and Paisley. Maddie left her hometown in the United States to do an internship in Barcelona for erotic filmmaker Erika Lust. Her new job, new colleagues and new friends offer Maddie a new perspective on life. After a few weeks, she is no longer the all-American girl she was when she arrived. Instead, she finds freedom and joy and self-love in Barcelona – and goes off the radar. Meanwhile, her sister Paisely is worried about Maddie's disappearance and makes it her mission to find her. She flies down to Barcelona to bring her younger sister back home. Will Paisley succeed or will she be lured into the heat of a European summer? This is a tale of sexual awakenings, erotic desire, curiosity and pleasure; this is a summer of Lust.